Five texture zeros and CP violation for the standard model quark mass matrices (2013)
ABSTRACT: The phenomenology of the five independent sets of 3 3 quark mass matrices with five texture zeros is carried through in full detail, including predictions for the CP-violation asymmetries. Our study is done without any approximation, first analytically and then numerically.